Developing and evaluation of an IoT mobile gateway for 4G LTE networks - Quiñones, Manuel Fernando; Pachar Bravo, Hever Patricio; Martínez-Curipoma, Javier; Quiñones , Luis; Torres , Rommel (Enfoque UTE, 2020)
The current trend is to connect everything to network to be monitored and controlled remotely through own concept IoT technologies. One of the problems is to connect the devices to a network, using technologies with sufficient coverage and capacity, so this article shows the development of a mobile gateway for IoT applications under the Android platform evaluated in 4G mobile networks. The IoT mobile gateway sends the data collected from sensors by selecting the MQTT and HTTP protocols, to IoT platforms on the Internet. The architecture is composed of temperature, luminosity and pressure sensors that are integrated into a sensor node which function is for data collection, processing and then via Bluetooth is sent to an Android smartphone where an application that performs the mobile gateway function is running, here data network are sent through the 4G LTE network to the IoT platforms of Ubidots and Watson IoT. Subsequently, tests were carried out with various metrics such as latency, energy consumption and connection costs. It concludes that IoT mobile gateway has better performance under MQTT protocol compared to HTTP.